Correlates of shopping orientation with retail choice decisions among young consumers - Safiek Mokhlis; Abdul Razak Kamaruddin; Sulaiman Md Yassin (Penerbit Universiti Kebangsaan Malaysia, 2003)
This paper attempts to investigate the relationship between adolescents' shopping orientation and their choice of retail purchases. Adolescents' shopping decisions comprised of two categories of retail institution, i.e., eating outlets and shopping centres. The data sample (N=934) was gathered from high school students at a number of schools in Terengganu and Selangor. Employing an area sampling approach, a survey was conducted among the respondents using a structured-type questionnaire. From the results of multiple regression analyses, several significant relationships were found between adolescents' shopping orientation and their choice of retail institutions. Adolescents would choose modern retail outlets when their motivations for consumption are stimulated by the desire for social and hedonistic reasons. On the other hand, when their motivations for consumption are reflected by the desire for getting the best value for their money, they tend to choose traditional retail outlets.